PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI BURNOUT SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pegawai KCP Bank BPD Jateng Di Kabupaten Pemalang) - DONNY INDRIYANTO; Grace Tianna Solovida (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This study aims to analyze the effect of workload and work environment on employee performance through burnout as an intervening variable. This research was conducted on employees KCP Bank BPD Jateng Di Kabupaten Pemalang. Sampling is done by saturated or census sampling because the population is only 60 respondents so that the entire population is taken as a sample. Data were collected using a questionnaire method. The results showed that workload statistically had no effect on employee performance. thecalculation results show that workload has an indirect effect on employee performance through burnout. Workload statistically has a positive and significant effect on burnout. the work environment statistically has no effect on employee performance. the calculation results show that the work environment has an indirect effect on employee performance through burnout. The work environment has a statistically significant and negative effect on burnout. Burnout has a statistically significant and negative effect on employee performance.